Br(V)-Induced Electron Transfer in Pentaamminecobalt(III) Complexes of α-Amino Acids - THAMINUM ANSARI, A.; SUBRAMANI, K. (Asian Journal of Chemistry, 2010)
Br(V) induced electron transfer in pentaamminecobalt(III) complexes of α-amino acids yielding 30 % of CO2, 30 % of Co(II) and 70 % of glyoxalato complex are ultimate products. The decrease in absorbance at 502 nm for Co(III) complex corresponds to nearly 40 % of the initial absorbance. Though the stoichiometry of Br(V) to unbound ligand is 1.0:0.6, the ratio of Br(V) to cobalt(III) complex is 1:0.3 accounting for about 40 % reduction at the cobalt(III) centre.The kinetic and stoichiometric results have been accounted by a suitable mechanism involving radical cation intermediate.